2020
DOI: 10.3390/agronomy10121863
|View full text |Cite
|
Sign up to set email alerts
|

Critical Leaf Magnesium Concentrations for Adequate Photosynthate Production of Soilless Cultured Cherry Tomato—Interaction with Potassium

Abstract: Magnesium (Mg) is essential to many plant physiological and biochemical processes; however, understanding how Mg nutrition quantitatively affects the production, partitioning, and utilization of photoassimilates is still lacking, especially in soilless culture systems. We focused on the roles of Mg in yield formation and interactions with potassium (K) nutrition of cherry tomato. Cherry tomato yield, photosynthetic parameters, dry matter weight, and K, Mg, and calcium (Ca) uptake were investigated in two soill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…The K:Mg accumulation ratio with excessive Mg application reduced plant growth, which may have been due to antagonism between the two elements when an imbalance was created. This phenomenon has been previously reported in cherry tomato [29] and pumelo [32]. Therefore, an unbalanced supply of Mg and K is not desirable because it affects plant growth, quality, and the distribution of nutrients across the plant [1].…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The K:Mg accumulation ratio with excessive Mg application reduced plant growth, which may have been due to antagonism between the two elements when an imbalance was created. This phenomenon has been previously reported in cherry tomato [29] and pumelo [32]. Therefore, an unbalanced supply of Mg and K is not desirable because it affects plant growth, quality, and the distribution of nutrients across the plant [1].…”
Section: Discussionmentioning
confidence: 64%
“…Mg fertilizer application enhanced Mg uptake in plants as well as the accumulation of other nutrients. Similarly, Mg application has been observed to promote N and P accumulation in rapeseed [25] and K and Ca uptake in cherry tomato (Lycopersicon esculentum) [29]. The application of Mg at a rate of 50 and 100 mg Mg/kg presented a K:Mg accumulation ratio of approximately 3:1, which has been demonstrated to be suitable for plant growth.…”
Section: Discussionmentioning
confidence: 93%
“…3), consequently its deficiency is directly related to the decrease in photosynthetic rates (Cakmak and Kirkby 2008). However, excess Mg may inhibit the transport of K of cytosol (Guan et al 2020), a study conducted with Hevea brasiliensis seedlings found a reduction in chlorophyll content and approximately 20% reduction in chloroplast length (Xue et al 2019). Regarding micronutrients, the absence of iron (Fe) interferes with metabolic processes, hormonal regulation, and enzymatic reactions (Krohling et al 2016).…”
Section: Impacts Of Nutritional Stress On Tree Growth Biochemical And...mentioning
confidence: 99%

How does soil nutritional stress limit restoration in the Amazon?

Isabella de Matos Rodrigues,
Bruno Rocha Martins,
Suelen da Silva Wanzerley
et al. 2023
ADV. FOR. SCI.
“…Research often indicates that increased K in crops may interact with other nutrients such as Mg and Ca [7][8][9], decreasing the uptake of these elements depending on the species. This situation impairs the growth of crops such as maize, potato, sugarcane, and cherry tomato [10][11][12][13]. Excess K is more likely to have an antagonistic effect with cations, but a synergistic effect can also take place.…”
Section: Introductionmentioning
confidence: 99%